PERAN KADER POSYANDU DALAM MENCEGAH STUNTING DI DUSUN SRUNGGO 2 SELOPAMIORO IMOGIRI BANTUL YOGYAKARTA - Sarni Anggoro; Eni Purwaningsih; Siti Hanifatun Fajria (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2025)
Stunting is a chronic nutritional problem that remains a major challenge to child health in Indonesia, including in Srunggo 2 Hamlet, Selopamioro, Imogiri, Bantul. Although the prevalence of stunting in the Special Region of Yogyakarta and Bantul Regency has shown a declining trend, prevention efforts still need to be strengthened through community-based health services such as Posyandu. Posyandu cadres play an important role in providing nutrition education, monitoring children’s nutritional status, and conducting interventions and family assistance to prevent stunting. However, the effectiveness of their role is strongly influenced by their capacity, training, and the support provided by the community and government. This study aims to explore the role of Posyandu cadres in Srunggo 2 Hamlet, Selopamioro, Imogiri, Bantul, Yogyakarta in preventing stunting. This research employed a qualitative approach through in-depth interviews, participatory observation, and focus group discussions (FGDs) to comprehensively understand the role of Posyandu cadres in stunting prevention in Srunggo 2 Hamlet. Thematic analysis was conducted to identify patterns, experiences, and challenges faced by the cadres in the field. Source triangulation and member checking techniques were used to ensure the validity of the data. The findings revealed six main themes: nutrition education, monitoring of children’s nutritional status, family-based approaches, collaboration with community health centers (puskesmas) and other institutions, cadre-led innovations, and community participation levels. Although cadres have actively played their roles, challenges such as limited training, inadequate facilities, and low attendance of mothers with toddlers hinder the optimal implementation of stunting prevention programs. This study concludes that strengthening the capacity of Posyandu cadres and cross-sectoral support is crucial to improving the effectiveness of stunting prevention efforts in Srunggo 2 Hamlet. Continuous efforts such as training, provision of facilities, and increased community participation are needed to reinforce Posyandu’s role as the frontline in stunting prevention at the village level